(untitled) (Journal of actual problems of jurisprudence, 2022)
In our opinion, environmental and legal culture can be with compliance of environmentally important activities with legal norms it should be understood as the state of individual and public consciousness that is characterized. This is the quality of norms, their knowledge in society, concept and interpretation, and also the environmental rights of a person in all legal ways protection of environmental tasks in everyday life and professional activities level of willingness to perform sustainable environmental and legal culture it depends on the level. Environmental education, education in the field of the environment one of the main and necessary conditions for sustainable development in the transmission system acts as a. When determining the goals of this issue, the most first, using scientific data in the local context and at the same time, paying special attention to professional training in this area, problems of education, the environment for all segments of the population development and development of the environment and implementation of concepts in the field of development in all curricula attention is paid to ensuring the needs of the population. Thus, environmental education is an immanent component of sustainable development all its basic provisions are clear or secretly introduces, as one of the most important tools to achieve the goal it is divided into two parts. Keywords: environmental legal order, environmental legislation, legal order, environmental law, environmental legal consciousness